Impacts of Lesion Characteristics on Procedures and Outcomes of Chronic Total Occlusion Recanalization With Antegrade Guidewire True Lumen Tracking Techniques: A Substudy of Taiwan True Lumen Tracking Registry - Chang, Chi-Jen; Liu, Shih-Chi; Tsai, Cheng-Ting; Cheng, Jen-Fang; Lee, Chien-Lin; Lin, Chia-Pin; Huang, Chi-Hung; Liou, Jun-Ting; Wang, Yi-Chih; Hwang, Juey-Jen (Frontiers in Cardiovascular Medicine, 2022)
Background: Lesion characteristics were shown to predict procedural success and outcome in CTO recanalization. However, diverse techniques involved might cause potential heterogeneity. Objective: The study aimed to test lesion impacts on chronic total occlusion (CTO) intervention with a pure antegrade wiring-based technique. Methods and Results: We studied consecutive 325 patients (64.5±11.1 years, 285 male) with native CTO lesions intervened by single operator with an antegrade-based technique between August 2014 and July 2020. Forty-seven patients with antegrade procedural failure (20 with pure antegrade wiring failure and 27 with back-up retrograde techniques) were compared to 278 patients with antegrade-only procedural success. With median follow-up of 30.8 (16.1-48.6) months, 278 patients with procedural success were further assessed for target vessel failure (TVF: cardiac death, target vessel myocardial infarction, target lesion revascularization). Patients with antegrade procedural success had lower percentage of history with bypass graft (4 vs. 15%, p=0.004), and lower J-CTO score (2.1±1.3 vs. 3.4±1.0, p<0.001), when compared to those with antegrade failure. The J-CTO score was independently associated with procedural failure (odds ratio=2.5, 95% CI=1.8-3.4) in multivariate analysis. However, only clinical features including female gender (hazard ratio: HR=4.3, 95% CI=1.4-13.1), estimated glomerular filtration rate< 60 ml/min/1.73m2 (HR=3.2, 95% CI=1.0-9.9), and old myocardial infarction (HR=4.5, 95% CI=1.5-12.8) could predict long-term TVF in multivariate Cox regression model. Conclusion: The feasibility of antegrade guidewire-crossing technique for native CTO intervention was highly determined by lesion characteristics. However, negligible lesion impacts on clinical prognosis in current study suggested the potential advantage of a simpler technique for CTO intervention.